Case Report: Primary splenic hydatid cyst - Wani, Bilal Ahmad; Khan, Mohammadd Ashraf; Baweja, Tanish; Shah, Omar Javed; Sumrani, Arushi; Rashid, Tajamul (Frontiers in Medicine, 2025)
IntroductionPrimary splenic hydatidosis accounts for <2% of global cystic echinococcosis (CE) cases. Its rarity and non-specific clinical presentation often lead to delayed diagnosis, increasing the risk of severe complications. This case is noteworthy because early clinical suspicion, despite subtle symptoms, enabled prompt diagnosis and successful treatment. It highlights the importance of maintaining a broad differential diagnosis when evaluating unexplained abdominal pain, particularly in endemic regions. We present this case along with a focused literature review to raise awareness and offer practical guidance for clinicians encountering similar diagnostic challenges.Case presentationA 23-year-old woman presented with chronic pain in the left upper quadrant of her abdomen, accompanied by nausea, vomiting, and low-grade fever. Physical examination revealed splenomegaly. Given her clinical presentation, a splenic hydatid cyst was considered as part of the differential diagnosis. Abdominal ultrasonography (USG) and computed tomography (CT) revealed a solitary cystic lesion in the spleen without calcification or solid components. Serological testing using enzyme immunoassay for IgG (Immunoglobulin G) and IgE (Immunoglobulin E) antibodies was positive for echinococcosis. Due to the large size of the cyst and the risk of rupture, a total splenectomy was performed. Histopathological examination of the resected specimen confirmed the diagnosis of a hydatid cyst. The postoperative course was uneventful, and the patient has continued to do well during regular outpatient follow-ups.ConclusionThis case highlights that splenic hydatid cysts, although uncommon and often presenting with non-specific symptoms, should be considered in the differential diagnosis of abdominal pain, especially in endemic regions. Early diagnosis through the combined use of imaging and serological tests is essential for effective clinical management. Surgical intervention, based on the cyst’s size and the risk of rupture, can result in excellent outcomes. This case underscores the need for heightened clinical suspicion in endemic regions to mitigate delays in diagnosis.